IMPLEMENTASI SAK EMKM GUNA PENYUSUNAN LAPORAN KEUANGAN PADA UMKM KOICA MILK SHOP KELURAHAN AIR DUKU KECAMATAN SELUPU REJANG - Meriana; Fery Fery (Politeknik Raflesia Press, 2022)
Financial Accounting Standards for Micro, Small and Medium Entities (SAK EMKM) have been stipulated by Law Number 20 of 2008 as a standard in the preparation of financial reports for Micro, Small and Medium Enterprises (MSMEs). applied in the financial statements of the MSME Koica Milk Shop, Air Duku Village, Selupu Rejang District. The method used in this research is descriptive qualitative method and data collection techniques are carried out using library research techniques and field studies. The data used are primary data and secondary data. Based on the data obtained, the authors found the problem is that the financial statements have not been prepared. The company only records incoming milk so that it only produces daily recap data. The results of this study indicate the preparation of financial statements at the MSME Koica Milk Shop, Air Duku Village, Selupu Rejang District which consists of a statement of financial position, income statement and notes to financial statements. The author suggests that the company should immediately implement the financial statements that the author has made based on SAK EMKM in order to assist in future decision making.